Desire change : contemporary feminist art in Canada - Davis, Heather M. (Heather Margaret) (McGill-Queen's University Press, 2017)
In the resistance to the violence of gender-based oppression, vibrant, but often ignored, worlds have emerged, full of nuance, humor and beauty. Correcting a glaring omission of writing about contemporary feminist work by Canadian artists, Desire Change considers the resurgence of feminist art, thought and practice in the past decade by examining artworks that respond to themes of diversity and desire. Essays by historians, artists and curators present an overview of a range of artistic practices including performance, installation, video, textiles and photography. Contributors address the desire for change through three central frames, how feminist art has significantly contributed to the complex understanding of gender as it intersects with sexuality and race, the necessary critique of patriarchy and institutions as they relate to colonization within the Canadian national-state and the ways in which contemporary critiques are formed and expressed. The resulting collection addresses art through an activist lens to examine intersectional feminism, decolonization and feminist institution building in a Canadian context. Heavily illustrated with representative works, Desire Change raises both the stakes and the concerns of contemporary feminist art, with an understanding that feminism is always and necessarily plural.